2018
DOI: 10.24264/icams-2018.xi.6
|View full text |Cite
|
Sign up to set email alerts
|

Life Cycle Assessment of Two Alternative End-of-life Scenarios for Leather Safety Shoes

Abstract: This paper provides a brief overview of the environmental impact of footwear industry and the end of life solutions. Nowadays almost 23 billion pairs of shoes are produced worldwide every year and most of them are landfilled after their use. Currently the lifetime of a pair of shoes is falling because of the customer preferences and the fast fashion trend at market and fashion industry. As a result, huge amounts of wastes are being landfilled. The aim of this paper is to analyses the environmental implications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In term of footwear production, China tops the chart with 14,200 million of footwear followed by India (2, 209 million), Brazil (900 million) and Vietnam (770 million). It was identified that only less than 5% of 20 billion pairs of shoes produced in a year is recycled whereas the remaining goes to incineration or landfill [29]. By understanding the CSR policy, a renowned sports shoe manufacturer Nike introduced a recycling program called ‗NikeGo Places'.…”
Section: Csr Of Leather Industriesmentioning
confidence: 99%
“…In term of footwear production, China tops the chart with 14,200 million of footwear followed by India (2, 209 million), Brazil (900 million) and Vietnam (770 million). It was identified that only less than 5% of 20 billion pairs of shoes produced in a year is recycled whereas the remaining goes to incineration or landfill [29]. By understanding the CSR policy, a renowned sports shoe manufacturer Nike introduced a recycling program called ‗NikeGo Places'.…”
Section: Csr Of Leather Industriesmentioning
confidence: 99%